2000
DOI: 10.1200/jco.2000.18.5.963
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Bone Marrow Transplantation for Therapy-Related Myelodysplastic Syndrome and Acute Myeloid Leukemia: A Long-Term Study of 70 Patients—Report of the French Society of Bone Marrow Transplantation

Abstract: BMT is an effective treatment for patients with t-MDS or t-AML who have responsive disease and, in particular, who have no poor-risk cytogenetic features. The poor results of the other patients, especially those with active disease at BMT, emphasize the need to delineate indications and perform prospective protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
130
6
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(147 citation statements)
references
References 35 publications
9
130
6
2
Order By: Relevance
“…It has been established that active disease at HCT leads to dismal outcomes. 5,8,22 Previously our group has reported that for each 10% increase in marrow blast percentage at the time of HCT, there is an increased risk of death by a factor of 1.21. 6 Here, we present preliminary evidence that success at reduction of disease burden holds potential as an important prognostic marker and might impact outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been established that active disease at HCT leads to dismal outcomes. 5,8,22 Previously our group has reported that for each 10% increase in marrow blast percentage at the time of HCT, there is an increased risk of death by a factor of 1.21. 6 Here, we present preliminary evidence that success at reduction of disease burden holds potential as an important prognostic marker and might impact outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, post transplant manipulation has been attempted, such as immune modulation with donor lymphocyte infusions or anti-leukemic therapy with hypomethylating agents. 7 Lower disease burden before HCT strongly correlates with improved outcome; 5,6,8,9 however, it is unknown if further cytotoxic salvage therapy before HCT improves outcomes or simply selects for chemosensitive patients. Prolonged pre-HCT treatment may lead to considerable toxicity and delay or eventually preclude HCT.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,[13][14][15][16] Here we present a retrospective long-term followup analysis of 79 unselected consecutive t-MDS/t-AML patients who underwent aHCT after predominantly RIC (73.4%) between 1995 and 2014. With a median follow-up of 7.5 years, this is one of the longest reported follow-up studies for this specific patient clientele, revealing a 10 year OS and DFS rate of 24% (13-36%) and 24% (14-36%), respectively, whereas the NRM rate was 32% (22-46%).…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16] Recent literature has indicated that performance status of transplant recipients, rather than recipient age per se, may be a better indicator of the ability of a patient to tolerate allo-HSCT. The Charlson comorbidity index, adapted for HSCT, has been shown to predict NRM in patients receiving allogeneic HSCT.…”
Section: Introductionmentioning
confidence: 99%